Prevalence of Hypocalcemia in Term Neonates with Moderate to Severe Birth Asphyxia in a Tertiary Care Hospital, Lahore - Atiqa; Shahzad, Qamar Uz Zaman; Arif Malik, Muhammad Ahmed; Siddique, Hira; Mukhtar, Nida; Amanat, Maria (Indus Journal of Bioscience Research, 2025)
Background: Birth asphyxia is a significant cause of neonatal morbidity and mortality. Hypocalcemia is a common metabolic complication in neonates with birth asphyxia, which may lead to severe consequences such as seizures and poor feeding. Objective: To assess the prevalence of hypocalcemia in term neonates with moderate to severe birth asphyxia and evaluate the associations between hypocalcemia and demographic/clinical variables. Methods: This cross-sectional study was conducted at the Neonatal Unit of the Department of Pediatric Medicine, Shalamar Hospital, Lahore, from 15 April 2024 to 15 October 2024. A total of 178 neonates with birth asphyxia were enrolled using a non-probability consecutive sampling technique. Data were collected on demographic characteristics, APGAR scores, serum calcium levels, and birth weight. Hypocalcemia was defined as serum calcium levels <7.5 mg/dL. Results: The prevalence of hypocalcemia in neonates with birth asphyxia was found to be 23.0%. A significant association was observed between low birth weight and hypocalcemia (p = 0.03), with 31.3% of low birth weight neonates showing hypocalcemia, compared to 16.0% of normal birth weight neonates. No significant differences were found between gender, mode of delivery, or APGAR scores and the prevalence of hypocalcemia. Conclusion: Hypocalcemia is prevalent in term neonates with moderate to severe birth asphyxia, particularly in those with low birth weight. Early screening for hypocalcemia and prompt intervention with calcium supplementation are crucial, especially for neonates with low birth weight, to prevent associated complications.